ANALYZING THE IMPACT OF TRAINING, CAREER DEVELOPMENT, AND REWARD SYSTEMS ON EMPLOYEE PERFORMANCE: THE ROLE OF EMPLOYEE ENGAGEMENT AS A MEDIATOR AT PT AFS - Haris Oky Adi Supinta; Asti Nur Aryanti; Nunung Ayu Sofiati; Gurawan Dayona Ismail (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study is motivated by performance issues identified among employees of PT Andalan Fluid Sistem, including delays in completing tasks, inconsistent achievement of work targets, frequent work errors, and reduced enthusiasm and organizational attachment. These symptoms indicate potential inefficiencies in the company’s training programs, career development practices, and reward system implementation. At the same time, employee engagement is considered a crucial psychological factor that bridges the relationship between human resource development initiatives and employee performance improvements. The study aims to analyze the influence of training, career development, and reward systems on employee performance, both directly and through employee engagement as a mediating variable. The conceptual framework is grounded in Human Capital Theory, Social Exchange Theory, and contemporary performance management concepts emphasizing the importance of employee emotional attachment to the organization. A quantitative explanatory design was employed. Data were collected using a Likert-scale questionnaire administered to employees of PT Andalan Fluid Sistem who met the research criteria. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to examine both the measurement and structural models, including tests of validity, reliability, multicollinearity, inner model evaluation, and assessments of direct and indirect effects. The findings indicate that training, career development, and reward systems influence employee performance, with varying levels of effect across variables. Employee engagement acts as a mediator in these relationships. The results emphasize that improving skills through training, providing clear career pathways, and applying a fair reward system can strengthen engagement and ultimately enhance performance. The study concludes that an integrated HR management strategy linking training, career development, reward systems, and engagement is essential. PT Andalan Fluid Sistem must ensure that HR development programs go beyond administrative functions by fostering employee motivation, loyalty, and emotional attachment as key drivers of improved performance.